2010
DOI: 10.2478/v10119-010-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of common reed (Phragmites australis) populations from selected lakes of Pomerania (NW Poland), revealed by electrophoretically detected peroxidase variability

Abstract: Genetic differentiation of common reed (Phragmites australis) populations from selected lakes of Pomerania (NW Poland), revealed by electrophoretically detected peroxidase variabilityThree populations of common reed (Phragmites australis(Cav) Trin. ex Steud.), growing under differing edaphic conditions in lakes near the town of Koszalin (the Pomerania region in north-western Poland), were studied in respect to frequencies of electrophoretically detected allozymes in two peroxidase loci: a monomeric locus with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several genetic studies at the population level conducted throughout Europe have consistently shown that genetic variance is distributed within, rather than among, populations, and that populations can be genetically very different from each other even at a local scale ( Lambertini et al 2008 ; Fér and Hroudová 2009 ; Paul et al 2011 ). However, isolation-by-distance patterns have failed to be detected ( Lambertini et al 2008 ; Fér and Hroudová 2009 ; Lukacs 2009 ; Krzakowa and Michalak 2010 ; Paul et al 2011 ) and, in general, lack of genetic structure seems to characterize the European continent ( Lambertini et al 2006 ). Phylogeographically, European Phragmites belongs to a group that extends throughout Eurasia and North America, as well as in the Southern Hemisphere in Africa and Australia ( Saltonstall 2002 ; Lambertini et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic studies at the population level conducted throughout Europe have consistently shown that genetic variance is distributed within, rather than among, populations, and that populations can be genetically very different from each other even at a local scale ( Lambertini et al 2008 ; Fér and Hroudová 2009 ; Paul et al 2011 ). However, isolation-by-distance patterns have failed to be detected ( Lambertini et al 2008 ; Fér and Hroudová 2009 ; Lukacs 2009 ; Krzakowa and Michalak 2010 ; Paul et al 2011 ) and, in general, lack of genetic structure seems to characterize the European continent ( Lambertini et al 2006 ). Phylogeographically, European Phragmites belongs to a group that extends throughout Eurasia and North America, as well as in the Southern Hemisphere in Africa and Australia ( Saltonstall 2002 ; Lambertini et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…This significant structure could be due to the high genetic diversity dispersed by the seeds of an octoploid allopolyploid. Lack of a regional geographic structure is a common feature of P. australis populations in Europe 29 31 , North America 32 and South Africa 33 . Even in Australia, Haplotype P populations are not genetically distinct 15 .…”
Section: Discussionmentioning
confidence: 99%